2013
DOI: 10.1159/000355517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Donepezil in Alzheimer Disease Can Be Measured by a Computerized Human Analog of the Morris Water Maze

Abstract: Background: Drug development for Alzheimer disease (AD) is challenged by the success in animal models tested in the Morris water maze (MWM) and the subsequent failures to meet primary outcome measures in phase II or III clinical trials in patients. The human variant of MWM (hMWM) enables us to examine allocentric and egocentric navigation as in the MWM. Objective: It was the aim of this study to examine the utility of a computerized hMWM to assess the effects of donepezil in mild AD. Methods: Donepezil 5 mg/da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…In this domain, spatial navigation tasks have been used as both an outcome variable (to assess the efficacy of clinical/pharmacologic intervention) and also as an intervention for possible cognitive/neural training. Pharmacological treatment of early AD with cholinergic agonists to reverse AD-related acetylcholine depletion has been found to enhance navigation performance in early AD (Hort et al, 2014) and to increase navigation-related hippocampal activation in MCI (Grön et al, 2006). In addition, behavioral interventions in the form of cognitive training may enhance cognitive performance in healthy elderly and also delay the onset or ameliorate the symptoms of dementia.…”
Section: Clinical Potential Of Spatial Navigationmentioning
confidence: 99%
“…In this domain, spatial navigation tasks have been used as both an outcome variable (to assess the efficacy of clinical/pharmacologic intervention) and also as an intervention for possible cognitive/neural training. Pharmacological treatment of early AD with cholinergic agonists to reverse AD-related acetylcholine depletion has been found to enhance navigation performance in early AD (Hort et al, 2014) and to increase navigation-related hippocampal activation in MCI (Grön et al, 2006). In addition, behavioral interventions in the form of cognitive training may enhance cognitive performance in healthy elderly and also delay the onset or ameliorate the symptoms of dementia.…”
Section: Clinical Potential Of Spatial Navigationmentioning
confidence: 99%
“…This was supported later in a follow-up study where hippocampal amnestic MCI patients showed no learning in the allocentric trials (Laczo et al, 2009). Virtual analogy was also used in a recent study (Hort et al, 2014), where BVA was termed Urania. Amnestic MCI were also impaired in another allocentric navigation test to find shortest way to hidden targets in a virtual park (Weniger et al, 2011).…”
Section: Spatial Navigation Deficits In MCI and Admentioning
confidence: 99%
“…Follow-up studies showed that spatial navigation testing using hMWM can identify amnestic MCI (aMCI) patients at high risk of conversion to dementia, specifically aMCI patients with a hippocampal type of memory impairment, who were similarly impaired in hMWM spatial test than patients with mild AD [10, 11]. Besides the human analog of the MWM, the computerized hMWM has also the potential to measure the effects of donepezil in mild AD and could be used as a sensitive cognitive outcome measure in AD clinical trials [12]. However, to the best of our knowledge, none of spatial navigation study was employed in patients with lacunar infarction.…”
Section: Introductionmentioning
confidence: 99%